Análisis de la gestión del riesgo de la banca múltiple en el Perú: 2000–2010 - Cortez Cortez, Gaby (2011)
The paper analyzes the risk management of banks that do business in Peru, through the application of indicators that relate the profitability of transactions with the risk. The RAROC (Risk adjusted Return on Capital) is one of the indicators associated with net income of an operation or set of operations of the bank in a year for capital at risk o economic capital. The versatility of this indicator allows to measure the bank ‘s risk management in a cross section, compared to other banks or a market benchmark, as well as to measure the evolution of risk management through a period of time compared to a RAROC target. The result shows that the Big Banks revealed a RAROC above the market average: 2.07 vs. 1.75. Medium Banks showed a RAROC below the overall average: 1.23 vs. 1.75. Finally Small Banks obtained an average ratio of 1.74 vs. 1.75, however within the period they showed a fluctuating behavior, above and below the average.